Adverse consequences Following COVID-19 Vaccination - Zayer, Raheem Hussein (South Asian Journal of Social Sciences and Humanities, 2023)
Background: Employing a potent preventive measure stands as the sole recourse against  COVID-19. The global scale of the COVID-19 pandemic has propelled an unparalleled rush  in vaccine development. This pressing demand has spawned a diverse range of approaches in  vaccine development considerations. Any potential adverse events from the COVID-19  vaccine are typical indicators that the body is building protection. Objectives: To identify the  prevalence, types and to investigate the possible attributed factors for the adverse events  associated with COVID-19 vaccines. Method: A descriptive cross-sectional study that was  conducted in the Iraq / Baghdad / Al-Resafa Directorate of Health (DOH) from the 7th of April  to the 5th of August 2021. A total of 420 participants were enrolled in the study. Results: The  most prevalent adverse events were injection site tenderness and joint pain /lethargy. There  was a significant association between the adverse event, time of disappearance, and the type of  vaccine, the highest percentage was associated with Pfizer BioNTech. The adverse events were  significantly higher in females. There was a significant association between the first and second  doses regarding the prevalence of injection site tenderness, joint pain, fever, and other adverse  events. Conclusion: Most vaccinated people developed mild adverse events, pain at the site of injection was the most prevalent adverse event. The gender and type of vaccine significantly  affected the development of the adverse events.
Keywords: COVID-19; vaccine; Adverse; Iraq; consequences